Características da população canina e felina da microrregião de Viçosa, Minas Gerais. II- zona rural - dos Santos , José Lúcio; de Faria , José Eurico; Carneiro , Luiz Hemetério D M; Viana , José Antônio; Ribeiro , Fernando José; B Ribeiro , Múcio Flávio; P da Silva , João Carlos (Revista Ceres, 2025)
A study of the canine and feline populations in the rural zone of the Viçosa microregion, Minas Gerais, was undertaken through of the analysis of a questionaire supplied to the owners of the animais during the anti-rabies vaccination realized in 1981.